2016
DOI: 10.1103/physrevphyseducres.12.020103
|View full text |Cite
|
Sign up to set email alerts
|

Examining and contrasting the cognitive activities engaged in undergraduate research experiences and lab courses

Abstract: While the positive outcomes of undergraduate research experiences (UREs) have been extensively categorized, the mechanisms for those outcomes are less understood. Through lightly structured focus group interviews, we have extracted the cognitive tasks that students identify as engaging in during their UREs. We also use their many comparative statements about their coursework, especially lab courses, to evaluate their experimental physics-related cognitive tasks in those environments. We find there are a number… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 19 publications
(31 reference statements)
0
35
0
3
Order By: Relevance
“…First, goals to reinforce content often come hand-in-hand with increased structure, as it becomes important for students to observe a particular "correct" result [2]. When one examines the cognitive activities in which students are engaged while completing such lab course activities [12,34], they are dominated by following instructions to collect specified data using unfamiliar equipment, and following specified procedures to analyze the data and write up reports in a specified format. Although the relevant physics concepts were central to the thinking of the instructor that designed and built the experiments, those concepts get little, if any, attention from the student carrying out the assigned activities using that apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, goals to reinforce content often come hand-in-hand with increased structure, as it becomes important for students to observe a particular "correct" result [2]. When one examines the cognitive activities in which students are engaged while completing such lab course activities [12,34], they are dominated by following instructions to collect specified data using unfamiliar equipment, and following specified procedures to analyze the data and write up reports in a specified format. Although the relevant physics concepts were central to the thinking of the instructor that designed and built the experiments, those concepts get little, if any, attention from the student carrying out the assigned activities using that apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that even small elements of open endedness in activities can improve student attitudes towards experimental physics [15]. Providing students with time, opportunity, and incentive to revise, troubleshoot, or explore by, for example, spreading a single lab experiment across multiple weeks may enable the desired skills focus [34,45]. Shifting the emphasis of the lab activities towards the quality of students' process rather than the product they obtain would be key to facilitating that development [34].…”
Section: Midterm Exammentioning
confidence: 99%
See 1 more Smart Citation
“…5 Although the finding may seem surprising at first, if you break down the elements of a typical lab activity, you realize that all the decision making involved in doing experimental physics is done for the students in advance. The relevant equations and principles are laid out in the preamble; students are told what value they should get for a particular measurement or given the equation to predict that value; they are told what data to collect and how to collect them; and often they are even told which buttons to press on the equipment to produce the desired output.…”
mentioning
confidence: 99%
“…We explored that mental terrain through an extended set of interviews with focus groups with 32 students who carried out undergraduate research over a summer semester; all the students had already taken the introductory physics lab sequence. 5 We asked them some general questions about their experiences in research, such as What are you enjoying the most? What are you learning?…”
mentioning
confidence: 99%